Efektivitas Program Lokasi Sementara (Loksem) Terhadap Penataan Pedagang Kaki Lima Di Ciracas Jakarta Timur - Susilawati Susilawati (JIAP (Jurnal Ilmu Administrasi Publik), 2019)
The Province of the Special Capital Region of Jakarta has been running the Temporary Location Program (LOKSEM) based on Governor Regulation Number 10 of 2015 for approximately three years. Temporary location (LOKSEM) is a place created by the government to accommodate and organize street vendors and to make it look orderly and neat. The street vendors who have occupied the Temporary Location Area (LOKSEM) will be fostered by the government so that they become more developed. The government also provides the necessary trading facilities and other additional facilities. The street vendors who were originally selling on the sides of the road are now neat and orderly due to the Temporary Location Program (LOKSEM). From the three years running, the results of this program have begun to be quite effective. The Temporary Location Program (LOKSEM), which has shown sufficiently effective results, is of course the driving and inhibiting factors faced. So that in the future the results achieved will be effective or not even effective. This research uses descriptive qualitative method with an inductive approach with data collection techniques using interview techniques, documentation, observation and triangulation and data analysis techniques using data reduction, data presentation, and drawing conclusions.